Nutraceutical Approach to Preventing Coronavirus Disease 2019 and Related Complications - Derosa, Giuseppe; Maffioli, Pamela; D’Angelo, Angela; Di Pierro, Francesco (Frontiers in Immunology, 2021)
Introductionː several months ago, an outbreak of pneumonia of unknown aetiology was detected in Wuhan city (China) and the aetiological agent of the atypical pneumonia was isolated by the Chinese authorities as novel coronavirus (2019-nCoV or SARS-CoV-2). The WHO announced this new disease was to be known as "COVID-19". Evidence acquisitionː when looking for new antiviral compounds, knowledge of the main viral proteins is fundamental. Several approaches are currently underway for the treatment of this disease, but a specific cure remains to be established. Evidence synthesisː the aim of this review is to describe how the use of selected nutraceuticals could be helpful, in addition to pharmacological therapy, in preventing some COVID-19-related complications in infected patients. Conclusionsː even if a specific and effective cure for COVID-19 still has some way to go, selected nutraceuticals could be helpful, in addition to pharmacological therapy, in preventing some COVID-19-related complications in infected patients.